FAKTORPENGHAMBAT SERTA PENDORONG PEREMPUAN UNTUK MAJU SEBAGAI CALON LEGISLATIF PADA PEMILU LEGISLATIF 2014 KABUPATEN MOJOKERTO - Totok Inwantoro; Yuwanto .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2014)
Election is one form of political participation . Every citizen has the right to participate in the General Election without exception . So also with women . Women's political participation is an important thing for the achievement of gender equality in politics , the involvement of women in public life has increased but unfortunately their participation and representation in the national legislature and provincial level , and in all government institutions remains low . Many of the Act has been made to increase the political participation of women , the latest is Law No. 5 of 2012 on the Election of Members of the DPR, DPD and DPRD . In addition to the low representation or the representation of women in political life in terms of number or quantity , then another picture accompanying it is a question of quality . The method used is descriptive qualitative research method , the research data obtained through interviews , documentation and library Studii . The low level of women's political participation in Mojokerto basically caused by several factors , including the political partaii awareness to help provide opportunities for women to participate in politics . A further factor is the quality of the women themselves , where most women have not had a quality that qualified as representatives in the parliament . The last factor is the patriarchal culture that resulted in the position of women is as a supplement in the political world .Keywords: Political Participation, Women, Legislative Election, Affirmative Action